11C-methionine PET aids localization of microprolactinomas in patients with intolerance or resistance to dopamine agonist therapy - Bashari, W. A.; van der Meulen, M.; MacFarlane, J.; Gillett, D.; Senanayake, R.; Serban, L.; Powlson, A. S.; Brooke, A. M.; Scoffings, D. J.; Jones, J.; O’Donovan, D. G.; Tysome, J.; et al. (Pituitary, 2022)
Purpose To assess the potential for 11 C-methionine PET (Met-PET) coregistered with volumetric magnetic resonance imaging (Met-PET/MR CR ) to inform clinical decision making in patients with poorly visualized or occult microprolactinomas and dopamine agonist intolerance or resistance. Patients and methods Thirteen patients with pituitary microprolactinomas, and who were intolerant ( n = 11) or resistant ( n = 2) to dopamine agonist therapy, were referred to our specialist pituitary centre for Met-PET/MR CR between 2016 and 2020. All patients had persistent hyperprolactinemia and were being considered for surgical intervention, but standard clinical MRI had shown either no visible adenoma or equivocal appearances. Results In all 13 patients Met-PET/MR CR demonstrated a single focus of avid tracer uptake. This was localized either to the right or left side of the sella in 12 subjects. In one patient, who had previously undergone surgery for a left-sided adenoma, recurrent tumor was unexpectedly identified in the left cavernous sinus. Five patients underwent endoscopic transsphenoidal selective adenomectomy, with subsequent complete remission of hyperprolactinaemia and normalization of other pituitary function; three patients are awaiting surgery. In the patient with inoperable cavernous sinus disease PET-guided stereotactic radiosurgery (SRS) was performed with subsequent near-normalization of serum prolactin. Two patients elected for a further trial of medical therapy, while two declined surgery or radiotherapy and chose to remain off medical treatment. Conclusions In patients with dopamine agonist intolerance or resistance, and indeterminate pituitary MRI, molecular (functional) imaging with Met-PET/MR CR can allow precise localization of a microprolactinoma to facilitate selective surgical adenomectomy or SRS.